(untitled) (Physical Education, Health and Social Sciences, 2026)
This article investigates the evolution of the Saraiki National Movement as a significant case study in regional persistence and democratic resilience within a multicultural federation. While conventional state-building often emphasizes centralized administrative control, this research argues that the mobilization of the Saraiki Waseb (Southern Punjab) represents a strategic community response to systemic "internal colonialism" and socio-economic marginalization. Drawing upon Benedict Anderson’s "imagined communities" and Michael Hechter’s "internal colonialism" models, the study utilizes a qualitative and descriptive methodology to analyze historical data, demographic shifts, and economic disparities between 1971 and 2026. The findings highlight a profound "agrarian paradox": while the Saraiki region provides the "white gold" (cotton) that serves as the backbone of Pakistan’s economy, it suffers from chronic underdevelopment, with poverty rates (43%) significantly exceeding the provincial average. The research further maps the transition of the movement from a cultural mood to a structured political demand through the role of grassroots institutions like Saraiki Lok Sanjh. These organizations have fostered community resilience by standardizing linguistic identity and creating inclusive social networks among the middle and labor classes. The article concludes that the quest for a separate Saraiki province—accelerated by contemporary catalysts like the 18th Amendment—is not a threat to state integrity but a necessary mechanism for federal stability. By addressing regional grievances through decentralization, the state can transform ethnic friction into a source of democratic strength, ensuring a more equitable and inclusive future for the federation.